Ecophysiological aspects and biomass production of soybean genotypes under soil flooding stress conditions - Silvana F. da Silva; Marcio de O. Martins; Paulo V. A. das Chagas; Gisele L. dos Santos; Aurélio P. Barros Júnior; Lindomar M. da Silveira; João E. da S. Ribeiro (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT The objective of this study was to evaluate the ecophysiological aspects and biomass production of three soybean genotypes subjected to soil flooding in the vegetative and/or reproductive stages. The design adopted was completely randomized with 5 replications, in a 3 x 3 factorial arrangement, with three soybean genotypes: PELBR 17-46, PELBR 15-7016, and 75I77RSF IPRO; and three water treatment conditions: soil flooding for 10 days in the vegetative period + 10 days in the reproductive period; soil flooding for 10 days only in the reproductive period, and the control treatment, where the soil was maintained at 70% of field capacity. There was a reduction in the relative water content for the PELBR 15-7016 and PELBR 17-46 genotypes in the vegetative/reproductive stages and in the reproductive stage, while for the 75I77RSF IPRO there was no difference. The levels of chlorophyll a, chlorophyll b, and total chlorophyll were reduced only for the PELBR 15-7016 and 75I77RSF IPRO genotypes. The dry matter in the leaves and roots was lower for PELBR 17-46 and PELBR 15-7016 when subjected to stress in the R2 soybean stage and for the grain production. PELBR 17-46 and PELBR 15-7016 genotypes are more susceptible to stress, while the 75I77RSF IPRO showed mechanisms to overcome waterlogging stress.